2017
DOI: 10.3390/ma10020172
|View full text |Cite
|
Sign up to set email alerts
|

Cooperativity of Spin Crossover Complexes: Combining Periodic Density Functional Calculations and Monte Carlo Simulation

Abstract: The total enthalpies of the 16 different spin configurations that can be realized in the unit cell of the archetype spin crossover complex [Fe(phen)2(NCS)2] (phen = 1,2-phenanthroline) were calculated, applying periodic density functional theory combined with the Hubbard model and the Grimme-D2 dispersion correction (DFT+U+D2). The obtained enthalpy differences between the individual spin configurations were used to determine spin couplings of an Ising-like model, and subsequent Monte Carlo simulations for thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 44 publications
(91 reference statements)
0
11
0
Order By: Relevance
“…Finally, we observed that the overall effect of the anharmonic correction was in general small enough to rely on the much simpler harmonic model, which gave direct estimates of the ZPE and ∆S without having to perform energy scans along the normal modes of the system under study. To proceed towards a computational strategy that is capable of reliably predicting transition temperatures for thermal spin crossover, it is more important to focus on a more sophisticated material model; environmental effects [64,65] and cooperativity [66,67] are expected to have a much larger influence than the anharmonic corrections.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we observed that the overall effect of the anharmonic correction was in general small enough to rely on the much simpler harmonic model, which gave direct estimates of the ZPE and ∆S without having to perform energy scans along the normal modes of the system under study. To proceed towards a computational strategy that is capable of reliably predicting transition temperatures for thermal spin crossover, it is more important to focus on a more sophisticated material model; environmental effects [64,65] and cooperativity [66,67] are expected to have a much larger influence than the anharmonic corrections.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, DFT calculations cannot evaluate Γ directly but only a configuration-dependent Γ-term that we label as Γ c and define as where H elec is the energy of configuration c relative to the LS state and Δ H HL is the energy difference between the all-HS and all-LS states (i.e., all molecules in the same spin state). This equation can be obtained starting from eq and assuming that only H elec contributes to cooperativity. , This is a good assumption considering how the remaining terms are usually evaluated computationally. Due to the size of the SCO molecules, exchange interactions between the metal spins are generally neglected, and the spins are regarded as completely localized.…”
Section: Methodsmentioning
confidence: 99%
“…This equation can be obtained starting from eq 1 and assuming that only H elec contributes to cooperativity. 40,41 This is a good assumption considering how the remaining terms are usually evaluated computationally. Due to the size of the SCO molecules, exchange interactions between the metal spins are generally neglected, and the spins are regarded as completely localized.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations